Uveal melanoma hepatic metastases mutation spectrum analysis using targeted next-generation sequencing of 400 cancer genes. Issue 4 (31st October 2014) - Luscan, A; Just, P A; Briand, A; Burin des Roziers, C; Goussard, P; Nitschké, P; Vidaud, M; Avril, M F; Terris, B; Pasmant, E
Abstract : Aims: Uveal melanoma (UM) is the most common malignant tumour of the eye. Diagnosis often occurs late in the course of disease, and prognosis is generally poor. Recently, recurrent somatic mutations were described, unravelling additional specific altered pathways in UM. Targeted next-generation sequencing (NGS) can now be applied to an accurate and fast identification of somatic mutations in cancer. The aim of the present study was to characterise the mutation pattern of five UM hepatic metastases with well-defined clinical and pathological features. Methods: We analysed the UM mutation spectrum using targeted NGS on 409 cancer genes. Results: Four previous reported genes were found to be recurrently mutated. All tumours presented mutually exclusive GNA11 or GNAQ missense mutations. BAP1 loss-of-function mutations were found in three UMs. SF3B1 missense mutations were found in the two UMs with no BAP1 mutations. We then searched for additional mutation targets. We identified the Arg505Cys mutation in the tumour suppressor FBXW7 . The same mutation was previously described in different cancer types, and FBXW7 was recently reported to be mutated in UM exomes. Conclusions: Further studies are required to confirm FBXW7 implication in UM tumorigenesis. Elucidating the molecular mechanisms underlying UM tumorigenesis holds the promise for novel and effective targeted UM therapies.